Social Media as a New Communication Platform in the Context of the Information Eco Strategy - Halyna Bryikhanova; Veronika Zaitseva; Iryna Gamova; Diana Fayvishenko (Journal of Information Technology Management)
The article is devoted to a comprehensive analysis of peculiarities of the content types, which can be placed in social media and Ukrainian Internet media, its differences, types of manipulation, and methods of prevention, perception, and distribution of unreliable information, determination of difference between fact and judgment. The article also analyzes the statistics of social media usage in Ukraine and around the world, using Facebook as an example. Various kinds and types of media existing on the Internet and traditional, conducted a survey of the most popular content using the Starch method, it was possible to identify how a person perceives one content that is placed on different media. The relationship between content type and media type is established. The phenomenon of information restriction, arising as a result of modern algorithms embedded in the Internet companies and social media, their positive and negative aspects and why, therefore, we are deprived of a choice among a wide range of other topics, and learning some other points of view was considered. Examining the origin and meaning of the "Information Bubble" term, the authors propose to use a different term, "Membrane of Relevance", which, in their opinion, is more relevant to the essence of the said concept. The authors propose to use a taxonomy method to determine the impact of content on a particular type of media, which will greatly simplify the content analysis process.